5a+6(a+7)=9

Simple and best practice solution for 5a+6(a+7)=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5a+6(a+7)=9 equation:


Simplifying
5a + 6(a + 7) = 9

Reorder the terms:
5a + 6(7 + a) = 9
5a + (7 * 6 + a * 6) = 9
5a + (42 + 6a) = 9

Reorder the terms:
42 + 5a + 6a = 9

Combine like terms: 5a + 6a = 11a
42 + 11a = 9

Solving
42 + 11a = 9

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-42' to each side of the equation.
42 + -42 + 11a = 9 + -42

Combine like terms: 42 + -42 = 0
0 + 11a = 9 + -42
11a = 9 + -42

Combine like terms: 9 + -42 = -33
11a = -33

Divide each side by '11'.
a = -3

Simplifying
a = -3

See similar equations:

| 2b-2=b+4 | | x+5=2x+3+x | | -8y-9=207 | | 2c-10=30 | | 3.2x=14 | | 4(0)+11y=7 | | 5.8-0.7=n | | 6r^2-3r^2-3r^2= | | 6/7=24-11 | | 3(5n-2)=-81 | | 4x+5=2+3.25 | | 4/9w=-12 | | -6c-4=-70 | | x/10-2=8 | | 4x+5=2+2.25 | | (4/3)x=36 | | 5u=4u+11 | | X(32/x) | | 8-3/5v=-7 | | (32/x) | | 5.87x+11.74=23.48 | | 0.08x=-6.4 | | 4q+1=4q-9 | | x-3(-1)=4 | | 6.6(x-1)=-0.4x+35.4 | | 2+r=7 | | 73-4=2 | | 6.67x+100=44.4889+10x | | -2y+7=77 | | 1=1/4x | | 5w-9w=56 | | 5+1*2= |

Equations solver categories